Effect of Sintering Temperature on Microstructure, Chemical Stability, and Electrical Properties of Transition Metal or Yb-Doped BaZr0.1Ce0.7Y0.1M0.1O3−δ (M = Fe, Ni, Co, and Yb) - Mirfakhraei, Behzad; Ramezanipour, Farshid; Paulson, Scott; Birss, Viola; Thangadurai, Venkataraman (Frontiers in Energy Research, 2014)
Perovskite-type BaZr0.1Ce0.7Y0.1M0.1O3-δ (M = Fe, Ni, Co and Yb) (BZCY-M) oxides were synthesized using the conventional solid-state reaction method at 1350-1550 oC in air in order to investigate the effect of dopants on sintering, crystal structure, chemical stability under CO2 and H2S, and electrical transport properties. The formation of the single-phase perovskite-type structure with an orthorhombic space group Imam was confirmed by Rietveld refinement using powder X-ray diffraction (PXRD) for the Fe, Co, Ni and Yb-doped samples. The BZCY-Co and BZCY-Ni oxides show a total electrical conductivity of 0.01 and 8 × 10-3 Scm-1 at 600 oC in wet H2 with an activation energy of 0.36 and 0.41 eV, respectively. Scanning electron microscopy (SEM) and energy-dispersive X-ray analysis (EDX) revealed Ba and Co rich secondary phase at the grain-boundaries, which may explain the enhancement in the total conductivity of the BZCY-Co. However, ex-solution of Ni at higher sintering temperatures, especially at 1550 oC, decreases the total conductivity of the BZCY-Ni material. The Co and Ni dopants act as a sintering aid and form dense pellets at a lower sintering temperature of 1250 oC. The Fe, Co and Ni-doped BZCY-M samples synthesized at 1350 oC show stability in 30 ppm H2S/H2 at 800 oC, and increasing the firing temperature to 1550 oC, enhanced the chemical stability in CO2 / N2 (1: 2) at 25-900 oC. The BZCY-Co and Ni compounds with high conductivity in wet H2 could be considered as possible anodes for intermediate temperature solid oxide fuel cells (IT-SOFCs).